Efek Mediasi Penggunaan Financial Technology Pada Pengaruh Literasi Keuangan Terhadap Inklusi Keuangan - Khusnah, Hidayatul; Sifa Imroatun Jannah; Mardiyah Anugraini (Jurnal Akuntansi, 2023)
This increasingly modern development continues to lead to the digitization of various sectors including economic activities, the emergence of financial technology can bring change and convenience to society but still does not increase financial inclusion and not a few people still do not understand financial literacy, and understanding of financial technology is still common. This study aims to find empirical evidence and analyze the mediating effect of the use of financial technology on the effect of financial literacy on financial inclusion. The sampling method used was purposive sampling method and the number of samples was 85 respondents who became the object of research. The data analysis method is in the form of quantitative descriptive analysis using primary data and hypothesis testing using WarpPLS 8.0 software. The test results show that financial literacy has no positive and insignificant effect on financial inclusion. Financial literacy has a positive and significant effect on financial technology. While financial technology has a positive and significant effect on financial inclusion, financial technology cannot mediate financial literacy on financial inclusion.